Banks in Portugal: service producers or financial intermediaries? - Martins, Ana Isabel (Tourism & Management Studies, 2011)
Financial and monetary intermediation is always been the core competencies of banks. However, to balance for the significant reduction in bank intermediation margins in recent years, institutions have promoted the increase of its charges, trough the supply of banking services and cross-selling techniques. DEA methodology was applied to the data of the 37 major banks operating in Portugal in 2007, according to the production and intermediation approaches, in order to identify best practices and the main causes of inefficiency. The main contribution of this study is the incorporation of new variables in the models that reflect, besides profitability, value creation and opportunity cost to shareholders. The efficiency is analyzed using a global perspective (including all banks) and by groups, based on homogeneity and risk factors. Separate frontiers are estimated and the inefficiencies intra-groups as differences among groups are also analyzed. The results show a tendency for banks to focus on certain skills. Overall, the average efficiency levels are low and significant waste of resources and inefficiencies of scale were registered.